2020
DOI: 10.3892/mmr.2020.11084
|View full text |Cite
|
Sign up to set email alerts
|

IgE and IgG4 responses to shrimp allergen tropomyosin and its epitopes in patients from coastal areas of northern China

Abstract: Sensitization to allergens and their peptides varies among patients due to geographical or ethnic differences. The present study aimed to investigate immunoglobulin (ig)e and igG 4 responses to tropomyosin and its peptides in shrimp allergic patients from northern china. a total of 92 subjects were studied, including 35 shrimp allergic patients, 29 patients with house dust mite (HdM) and/or cockroach allergic patients and 28 healthy volunteers. Serum ige and igG 4 antibodies to recombinant shrimp tropomyosin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…These follow-up appointments also provide opportunities for healthcare professionals to reinforce treatment recommendations and educate patients on the importance of treatment adherence. 34 , 35 Patients should also be encouraged to actively seek knowledge and engage in self-management of their condition. Support groups and online forums can facilitate information exchange and provide a sense of community among patients.…”
Section: Discussionmentioning
confidence: 99%
“…These follow-up appointments also provide opportunities for healthcare professionals to reinforce treatment recommendations and educate patients on the importance of treatment adherence. 34 , 35 Patients should also be encouraged to actively seek knowledge and engage in self-management of their condition. Support groups and online forums can facilitate information exchange and provide a sense of community among patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that the number of peptides recognized by IgE was moderately correlated with the level of egg-sIgE ( r = 0.414, P < 0.01), which was similar to the result of the previous study. 14 24 Patients with a history of cutaneous symptoms alone recognized a significantly smaller number of epitopes than those with a history of more severe multiple organ system reactions. There was a significant correlation between the number of IgE epitopes of OVM and historical reactivity ( r = 0.706, P < 0.01), epitope studies on other allergens have yielded similar results.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, allergen-related IgG4 antibodies are thought to be involved in the development of clinical tolerance, and the mechanism of its immunoprotective effect is that IgG4 can compete with IgE for binding to allergen epitopes, thereby blocking IgE-mediated allergic reactions. 32 , 33 , 34 It has also been suggested that allergen-associated IgG is an incidental phenomenon and has nothing to do with function. 35 It is known that the incidence of food allergies such as egg and milk allergy in adults is much lower than that in children, and the serum IgG4 test results in this study showed that up to 50% of the individuals were positive for egg IgG4.…”
Section: Discussionmentioning
confidence: 99%